2020
DOI: 10.1093/ejcts/ezaa050
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of preoperative bronchoscopic marking for pulmonary nodules

Abstract: OBJECTIVES Recent studies have suggested the usefulness of preoperative bronchoscopic marking techniques for the localization of pulmonary nodules in thoracic surgery. This systematic review and meta-analysis aimed to evaluate the efficacy and safety of preoperative bronchoscopic marking. METHODS The PubMed and Cochrane Library databases were searched for clinical studies evaluating preoperative bronchoscopic marking for pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…The second is the need for special equipment [ 6 ]. VAL-MAP requires a catheter and virtual bronchoscopic navigation, and the ICG injection requires near-infrared thoracoscopy [ 6 , 13 ]. Although the hybrid technique is relatively costly, we believe that accomplishing an ideal extended segmentectomy is worth the cost of special equipment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second is the need for special equipment [ 6 ]. VAL-MAP requires a catheter and virtual bronchoscopic navigation, and the ICG injection requires near-infrared thoracoscopy [ 6 , 13 ]. Although the hybrid technique is relatively costly, we believe that accomplishing an ideal extended segmentectomy is worth the cost of special equipment.…”
Section: Discussionmentioning
confidence: 99%
“…VAL-MAP is a safe, efficacious, bronchoscopic, multiple pulmonary dye-marking technique that uses virtual bronchoscopic navigation [ 7 , 13 ]. It can be used to create multiple marks near the tumor that allow accurate identification of the tumor during subsequent surgery [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among localization techniques, virtualassisted lung mapping (VAL-MAP), a bronchoscopic preoperative multi-spot dye marking technique, 1 is highly safe and reproducible. [2][3][4][5] Notably, the multiple dye marks of VAL-MAP are designed to indicate sufficient resection margins, 1,6 which have a significant impact on local recurrence and patient survival in sublobar lung resection. 7,8 However, because the information provided by the dye marks is limited to the pleural surface, acquiring deep resection margins is a major concern.…”
Section: Perspectivementioning
confidence: 99%
“…A recent meta-analysis by Yanagiya et al showed success rates of dye marking, intraoperative localization and complete resection of over 95% with the use of ENB. 15 Although most studies have been done using the superDimension system, the SPiN platform can be used in a similar fashion for this purpose with the potential advantage of using the SPiN Perc tool for peripheral lesions abutting the pleural surface or those that are not reached with the endobronchial approach.…”
Section: Spin Thoracic Navigation System™mentioning
confidence: 99%